Ibuprofen for Ductus Arteriosus Months after Birth - Odile Frauenfelder; Ingrid M. van Beynum; Irwin K. M. Reiss; Sinno H. P. Simons (Case Reports in Pediatrics)
Ibuprofen is a well-known agent used to treat patent ductus arteriosus in preterm neonates in the first days of life. In the current case report we illustrate the potential use of ibuprofen in two preterm neonates 60 and 88 days after birth, respectively. To our knowledge, this is the first report on the effects of ibuprofen on patent ductus arteriosus in preterm newborns after months of life. These cases suggest that the ductus arteriosus does not become refractory for ibuprofen after the first days of life. Late closure of the duct with ibuprofen might still improve the cardiorespiratory condition and prevent infants from surgical closure. Controlled trials are necessary to further study these findings.